First‐line pembrolizumab for non–small cell lung cancer patients with PD‐L1 ≥50% in a multicenter real‐life cohort: The PEMBREIZH study. (5th February 2020) - Amrane, Karim; Geier, Margaux; Corre, Romain; Léna, Hervé; Léveiller, Guillaume; Gadby, Florence; Lamy, Régine; Bizec, Jean‐Louis; Goarant, Eric; Robinet, Gilles; Gouva, Sylvie; Quere, Gilles; et al.
Abstract: Background: The KEYNOTE‐024 trial demonstrated that pembrolizumab, a PD‐1 inhibitor, significantly improves progression‐free survival (PFS) and overall survival (OS) in selected patients with previously untreated advanced non–small cell lung cancer (NSCLC) with a PD‐L1 tumor proportion score (TPS) ≥50% and without EGFR/ALK aberrations. The main aim of this study was to report the efficacy and safety profile of pembrolizumab in real‐life conditions. Method: This was a French retrospective multicenter longitudinal study of 108 consecutive patients with advanced NSCLC, a PD‐L1 TPS ≥50% and without EGFR/ALK aberrations who were treated by pembrolizumab, in first line. Patient data were obtained from medical files. Results: The main characteristics of the cohort were: median age [range] 66.7 [37‐87] years, 64.8% male, 23.1% with a performance status (PS) of 2, and 88.9% current or former smokers. Eighty‐seven percent had stage IV NSCLC at diagnosis, 9.2% untreated brain metastases at inclusion, . With a median follow‐up of 8.2 months, the median PFS was 10.1 months (95% CI, 8.8‐11.4). The objective response rate was 57.3% (complete response 2.7%, partial response 54.6%). Disease control rate was 71.1%. At 6 months, the OS rate estimated was 86.2%. Treatment‐related adverse events (AE) of grade 3 occurred in 8% of patients. There were no grade 4 or 5 AEs. Conclusion: In a real‐life cohort of advanced NSCLC patients (including PS 2 and untreated brain metastases), with PD‐L1 TPS ≥50%, pembrolizumab demonstrates similar PFS to the pivotal clinical trial. Abstract : This retrospective multicenter longitudinal study was intended to report the efficacy and safety profile of pembrolizumab in real‐life conditions for the first‐line treatment of advanced squamous none small‐cell lung cancer. The median progression free survival was 10.1 months (95% CI, 8.8‐11.4) and the treatment‐related adverse events of grade 3 occurred in 8% of patients. This study demonstrates similar progression‐free survival to KEYNOTE‐024.